The EBI Search engine: providing search and retrieval functionality for biological data from EMBL-EBI - Squizzato, Silvano (Nucleic Acids Res, 2015)
The European Bioinformatics Institute (EMBL-EBI—https://www.ebi.ac.uk) provides free and unrestricted access to data across all major areas of biology and biomedicine. Searching and extracting knowledge across these domains requires a fast and scalable solution that addresses the requirements of domain experts as well as casual users. We present the EBI Search engine, referred to here as ‘EBI Search’, an easy-to-use fast text search and indexing system with powerful data navigation and retrieval capabilities. API integration provides access to analytical tools, allowing users to further investigate the results of their search. The interconnectivity that exists between data resources at EMBL-EBI provides easy, quick and precise navigation and a better understanding of the relationship between different data types including sequences, genes, gene products, proteins, protein domains, protein families, enzymes and macromolecular structures, together with relevant life science literature.